Comparative Finite Element Analysis of Exoskeletons Materials for Durability in Rehabilitation (Recoletos Multidisciplinary Research Journal, 2025)
Background: Assistive devices, such as exoskeletons, are one of the biggest breakthroughs in the medical industry, especially regarding physical therapy and rehabilitation. However, many of these devices are expensive. Due to this, one of the many concerns consumers have about these assistive devices is their durability and longevity. As such, there is a need to ensure that these devices are durable enough to handle a significant amount of use. Methods: One way to ensure the durability of these devices is to use quality materials when creating them. This paper tackles this further, wherein three materials, namely aluminum, stainless steel, and titanium, are tested in two exoskeleton models, wherein nine tests per model were done. The models are inputted into the ANSYS software and tested using the ?Static Structural? analysis system. These models? stress, strain, and deformation values are then obtained and analyzed.Results: The results are then compared with one another and then ranked accordingly. Conclusion: The study concluded that aluminum is the best primary material for exoskeletons due to its resulting mechanical properties. It should be noted, however, that both models had different results for their best material, showing that, although aluminum would be the best overall material, the best material would still depend on the model?s size, shape, and purpose, which aligns with the hypothesis of the study.
Keywords: deformation; finite element analysis; physical therapy; rehabilitation; stress-strain